Fanners' Level of Satisfaction with Farm Inputs Services in Oyo State, Nigeria - A B Ogunwale; C O Oladosu; E A Laogun (Journal of Agricultural Extension, 2015)
The study investigated farmers' level of satisfaction with inputs support service. Data were collected on sources of farm inputs, preferred sources of inputs and levels of satisfaction with input services from randomly selected 136 fanners in the five local government areas within Ogbomoso Zone of Oyo State Agricultural Development Programme. Frequencies and percentages, and analysis of variance (ANOVA) were used in data analysis. Farmers are most satisfied with improved planting materials. However, farmers are not satisfied with fertilizer procurements, agro -chemicals and tractor hiring services in the stale. It has been statistically established that there is no significant difference in the levels of fanners' satisfaction with input support services. It is recommended that government should establish drop points at grass -roots level and reduce cost of farm Inputs and services.